Resilience and Hopelessness: Exploring the Mediator Role of Spirituality in the Global Situation of COVID-19 - Hafza Aroosa Maraj; Hakan Gülerce; Shehnaz Rana; Munazzah Meraj (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2020)
This research aims to describe and to define the importance of spirituality as a mediator in the global pandemic situation of COVID-19 in Pakistan while having positive correlation with resilience and inverse with hopelessness. The correlational research design was used and data was gathered by simple random sampling and there was a use of standardized psychological instruments to measure the variables. The participants were (N=540) Pakistani general population (male and female) with the age range of 18–60. The outcomes revealed that resilience was positively correlated with spirituality (r=0.72; p <0.01) while spiritualty is negatively correlated with hopelessness (r=-0.76; p <0.01) and resilience was negatively correlated with hopelessness (r=-0.78, p <0.01). Mediation analysis shows that spirituality performed a strong intermediating role between resilience and hopelessness the direct effect of hopelessness on resilience was -5.9** whereas the indirect effect through spirituality was -1.7** and the total effect size was – 7.6**. It is revealed that spirituality has a strong impact on the resilience behavior and reduces the hopelessness even in the worldwide disastrous situation. This study enhances the literature related to the psychological research and prompts the role of spiritual coping strategies especially in the state of uncertainty like coronavirus pandemic.